Comercializacion de la leche y sus derivados en el municipio de Chalco, Edo, de Mexico - Vargas Oropeza, J.A.=700 1 Flores Parra, J.G.; Ramirez Vaca, J.J.
(Es, En)
Ilus., 16 ref.
Keywords: PRODUCCION LECHERA; PRODUCTOS LACTEOS; MERCADEO; MEXICO; REVISTA CHAPINGO